An Ecosystem Approach, the Acoustic Assessment of the Northern Demersal Scalefish Fishery – Distribution, Habitat and Abundance - Gastauer, Sven (Curtin University, 2017)
Fisheries acoustics are one of the most promising tools for holistic marine monitoring. Modern fishing vessels, equipped with echosounders, can be used as scientific platforms. Acoustic data and optical catch recordings were collected opportunistically in the Northern Demersal Scalefish Fishery. Acoustic scattering properties of key species were estimated and it was shown that abundance, biomass, habitat, hotspot and acoustic diversity indices can be extracted from such data. Precision estimates can be established using geostatistics.